Kontribusi Minat Baca Cerpen dan Penguasaan Kosakata terhadap Keterampilan Menulis Cerpen Siswa Kelas X MAN 1 Padang - Liga Febrina; Ermanto .; Irfani Basri (Bahasa, Sastra, dan Pembelajaran, 2013)
Abstract: This research is form the background of several phenomenon. First, lack of encouragement from the teacher or the surrounding environment on the importance of reading. Second, limited means, such as the lack of availability of books in the library. Third, uninteresting reading materials and the students are not accustomed to read. Fourth, the lack of student awareness of the importance of reading. Starting from those phenomenons, this study aims to determine the contribution of reading interest short story and mastery of vocabularies to the student’s short story. The method that is used in this research is correlation analition. The hypothesis in this  research is contribution of reading interest short story toward writing short story is very significance, contribution in understanding toward writing short story, contribution reading interst short story and understanding join together in writing short story. So, overall reading interest short story and mastery of vocabularies to  the student’s ability at Grade X  MAN 1 Padang. Kata kunci: minat baca cerpen, penguasaan kosakata, keterampilan menulis cerpen